2011
DOI: 10.1021/bc200078p
|View full text |Cite
|
Sign up to set email alerts
|

Novel DOTA-Neurotensin Analogues for 111In Scintigraphy and 68Ga PET Imaging of Neurotensin Receptor-Positive Tumors

Abstract: Overexpression of the high affinity neurotensin receptor 1 (NTSR1), demonstrated in several human cancers, has been proposed as a new marker for human ductal pancreatic carcinoma and as an independent factor for poor prognosis for ductal breast cancer, head and neck squamous cell carcinoma, and non-small cell lung cancer. The aim of the present study was to develop new DOTA-neurotensin analogues for positron emission tomography (PET) imaging with (68)Ga and for targeted radiotherapy with (90)Y or (177)Lu. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
95
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(112 citation statements)
references
References 40 publications
6
95
1
Order By: Relevance
“…It seems that the exchange reaction of tricine with plasma proteins is a major reason of protein binding, and it is not related to structural conformational changes caused by the BFCAs. [24] The radioconjugate showed nanomolar affinity toward the NTR receptor (32.66 ± 4.01 nm), but this affinity is worse than affinities reported for this pharmacophore by Alshoukr et al [19] This deficiency probably is due to the addition of β-alanine in the structure of peptide and not related to changes performed in radiometal, BFCA, and coligands. Alshoukr et al have reported similar affinities for this pharmacophore through labeling by different radioisotopes and BFCA (16 ± 2 nm for 111 In-DTPA-NT-20.3a, 15 ± 1 nm for 111 In-DOTA-NT-20.3 and 14 ± 2 nm (68) Ga-DOTA-NT-20.3).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…It seems that the exchange reaction of tricine with plasma proteins is a major reason of protein binding, and it is not related to structural conformational changes caused by the BFCAs. [24] The radioconjugate showed nanomolar affinity toward the NTR receptor (32.66 ± 4.01 nm), but this affinity is worse than affinities reported for this pharmacophore by Alshoukr et al [19] This deficiency probably is due to the addition of β-alanine in the structure of peptide and not related to changes performed in radiometal, BFCA, and coligands. Alshoukr et al have reported similar affinities for this pharmacophore through labeling by different radioisotopes and BFCA (16 ± 2 nm for 111 In-DTPA-NT-20.3a, 15 ± 1 nm for 111 In-DOTA-NT-20.3 and 14 ± 2 nm (68) Ga-DOTA-NT-20.3).…”
Section: Discussionmentioning
confidence: 85%
“…Based on the research of Alshoukr et al, the stability and pharmacokinetic of NT analogues were improved by substitution of Ile residue with Tle (on the cleavage bond 11-12). [2,19] In this research,…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The 13 a.a.r. peptide neurotensin (ELYENKPRRPYIL) is a neurotransmitter as well as neuromodulator in the brain and a paracrine or circulating hormone in the periphery [110] [111]. Neurotensin is facilitating pain if applied in low doses (0.03 pM -0.03 nM; [119] [120]) to the rostral ventromedial medulla (RVM) [121] but revealed an analgesic effect at higher dosage [10].…”
Section: Neurotensin and Neurotensin Receptorsmentioning
confidence: 99%